Made for each other - Cromwell, John, 1888-1979; Lombard, Carole, 1908-1942; Stewart, James, 1908-1997; Selznick International Pictures; Cinetel Films ([Hollywood, CA] : Selznick International Pictures, Inc., 1939)
Young lawyer meets and marries girl after knowing her one day. Takes bride home to meet his mother who disapproves of the marriage. Lawyer thinks everything will be fine as he moves up the ladder of the law firm. He doesn't and things get tough. A baby makes things even tougher. --
Carole Lombard, James Stewart, Charles Coburn, Lucile Watson, Eddie Quillan, Alma Kruger.
Photography, Leon Shamroy; editor, James E. Newcom; music, Oscar Levant.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Married people -- Drama; Parent and child -- Drama; Man-woman relationships -- Drama; Couples -- Drama; Comedy films; Feature films; Romantic comedy films; Internet videos; Streaming video